Nourishing the Social Innovation Debate with the “Social Technology” South American Research Tradition - Pozzebon, Marlei; Tello-Rozas, Sonia; Heck, Isabel (Voluntas, 2021)
Inspired by the South American research tradition known as “social technology,” this article proposes an operational framework to advance the understanding of mechanisms that help to promote social transformation. To illustrate its theorizing potential, we apply the framework to a nonprofit organization–Parole d’excluEs–that was created in Montreal (Canada) in 2006 and that has been promoting citizen mobilization and commitment to social change (parole-dexclues.ca). To that end, we offer a theoretical paper with an empirical illustration as a first step in a reflection on employing a global South theoretical lens–drawing on the concept of social technology–to make sense of a global North social innovation experience and to advance existing knowledge on the mechanisms of social transformation. The results contribute to social innovation research and practice, particularly at the interface between the management and nonprofit literatures.
N'AVONS PAS ACCÈS
Keywords: Amérique centrale/sud; Amérique latine; Canada; Changement social; Innovation sociale; Montréal; Nord / Sud; Recherche; Technologie sociale; Transformations

Nourishing the Social Innovation Debate with the “Social Technology” South American Research Tradition - Marlei, Pozzebon; Tello-Rozas, Sonia; Heck, Isabel (Voluntas, 2021)
Inspired by the South American research tradition known as “social technology,” this article proposes an operational framework to advance the understanding of mechanisms that help to promote social transformation. To illustrate its theorizing potential, we apply the framework to a nonprofit organization–Parole d’excluEs–that was created in Montreal (Canada) in 2006 and that has been promoting citizen mobilization and commitment to social change (parole-dexclues.ca). To that end, we offer a theoretical paper with an empirical illustration as a first step in a reflection on employing a global South theoretical lens–drawing on the concept of social technology–to make sense of a global North social innovation experience and to advance existing knowledge on the mechanisms of social transformation. The results contribute to social innovation research and practice, particularly at the interface between the management and nonprofit literatures.
Number: 3 N'AVONS PAS ACCÈS
Keywords: Amérique latine; Canada; Changement social; Innovation sociale; Montréal; Recherche; Technologie sociale; Transformations

Laboratoires vivants en innovation sociale et coconstruction des connaissances dans les villes : les cas du TIESS (Montréal) et de l’OBISF (Florianópolis) - Magalhaes, Thiago; Camus, Annie; Andion, Carolina; Tello-Rozas, Sonia (Revue Organisations & territoires, 2020)
Le débat sur le rapport entre l’innovation sociale et les villes s’est élargi au cours des dernières décennies. Ce débat met en évidence l’intérêt suscité par les processus de coconstruction des savoirs dans les laboratoires vivants en innovation sociale (LVIS). Cet article a pour objectif de présenter une approche conceptuelle et analytique du traitement des LVIS, ainsi que de décrire et de mettre en perspective deux expériences de mise en oeuvre de LVIS dans les villes : l’Observatoire de l’innovation sociale de Florianópolis (OBISF) au Brésil et Territoires innovants en économie sociale et solidaire (TIESS) à Montréal au Canada. Bien qu’ils émergent dans des réalités et des contextes différents avec des méthodologies de mise en oeuvre spécifiques, qui sont présentées dans le texte, la discussion et l’analyse des deux cas apportent des pistes d’apprentissage sur les défis et les perspectives quant à la coconstruction des connaissances visant à renforcer les dynamiques d’innovation sociale à l’échelle d’une ville.
Number: 2
Keywords: Brésil; Canada; Co-construction; Laboratoire vivant; Réservé UdeM; Urbanisme; Économie sociale; Économie solidaire

Laboratoires vivants en innovation sociale et coconstruction des connaissances dans les villes : les cas du TIESS (Montréal) et de l’OBISF (Florianópolis) - Magalhaes, Thiago; Camus, Annie; Andion, Carolina; Tello-Rozas, Sonia (Revue Organisations & territoires, 2020)
Le débat sur le rapport entre l’innovation sociale et les villes s’est élargi au cours des dernières décennies. Ce débat met en évidence l’intérêt suscité par les processus de coconstruction des savoirs dans les laboratoires vivants en innovation sociale (LVIS). Cet article a pour objectif de présenter une approche conceptuelle et analytique du traitement des LVIS, ainsi que de décrire et de mettre en perspective deux expériences de mise en oeuvre de LVIS dans les villes : l’Observatoire de l’innovation sociale de Florianópolis (OBISF) au Brésil et Territoires innovants en économie sociale et solidaire (TIESS) à Montréal au Canada. Bien qu’ils émergent dans des réalités et des contextes différents avec des méthodologies de mise en oeuvre spécifiques, qui sont présentées dans le texte, la discussion et l’analyse des deux cas apportent des pistes d’apprentissage sur les défis et les perspectives quant à la coconstruction des connaissances visant à renforcer les dynamiques d’innovation sociale à l’échelle d’une ville.
Number: 2
Keywords: Brésil; Canada; Co-construction; Laboratoire vivant; Living Labs; Montréal; Réservé UdeM; Urbanisme; Économie sociale; Économie solidaire